The Signatures of Natural Selection and Molecular Evolution in Fusarium graminearum Virus 1 - Heo, Jeong-In; Yu, Jisuk; Choi, Hoseong; Kim, Kook-Hyung (Frontiers in microbiology, 2020)
Fusarium graminearum virus 1 (FgV1) is a positive-sense ssRNA virus that confers hypovirulence in its fungal host, Fusarium graminearum. Like most mycoviruses, FgV1 exists in fungal cells, lacks an extracellular life cycle, and is therefore transmitted during sporulation or hyphal anastomosis. To understand FgV1 evolution and/or adaptation, we conducted mutation accumulation (MA) experiments by serial passage of FgV1 alone or with FgV2, 3, or 4 in F. graminearum. We expected that the effects of positive selection would be highly limited because of repeated bottleneck events. To determine whether selection on the virus was positive, negative, or neutral, we assessed both the phenotypic traits of the host fungus and the RNA sequences of FgV1. We inferred that there was positive selection on beneficial mutations in FgV1 based on the ratio of non-synonymous to synonymous substitutions (d N /d S ), on the ratio of radical to conservation amino acid replacements (p NR /p NC ), and by changes in the predicted protein structures. In support of this inference, we found evidence of positive selection only in the open reading frame 4 (ORF4) protein of DK21/FgV1 (MA line 1); mutations at amino acids 163A and 289H in the ORF4 of MA line 1 affected the entire structure of the protein predicted to be under positive selection. We also found, however, that deleterious mutations were a major driving force in viral evolution during serial passages. Linear relationships between changes in viral fitness and the number of mutations in each MA line demonstrated that some deleterious mutations resulted in fitness decline. Several mutations in MA line 1 were not shared with any of the other four MA lines (PH-1/FgV1, PH-1/FgV1 + 2, PH-1/FgV1 + 3, and PH-1/FgV1 + 4). This suggests that evolutionary pathways of the virus could differ with respect to hosts and also with respect to co-infecting viruses. The data also suggested that the differences among MA lines might also be explained by mutational robustness and other unidentified factors. Additional research is needed to clarify the effects of virus co-infection on the adaptation or evolution of FgV1 to its environments.Fusarium graminearum virus 1 (FgV1) is a positive-sense ssRNA virus that confers hypovirulence in its fungal host, Fusarium graminearum. Like most mycoviruses, FgV1 exists in fungal cells, lacks an extracellular life cycle, and is therefore transmitted during sporulation or hyphal anastomosis. To understand FgV1 evolution and/or adaptation, we conducted mutation accumulation (MA) experiments by serial passage of FgV1 alone or with FgV2, 3, or 4 in F. graminearum. We expected that the effects of positive selection would be highly limited because of repeated bottleneck events. To determine whether selection on the virus was positive, negative, or neutral, we assessed both the phenotypic traits of the host fungus and the RNA sequences of FgV1. We inferred that there was positive selection on beneficial mutations in FgV1 based on the ratio of non-synonymous to synonymous substitutions (d N /d S ), on the ratio of radical to conservation amino acid replacements (p NR /p NC ), and by changes in the predicted protein structures. In support of this inference, we found evidence of positive selection only in the open reading frame 4 (ORF4) protein of DK21/FgV1 (MA line 1); mutations at amino acids 163A and 289H in the ORF4 of MA line 1 affected the entire structure of the protein predicted to be under positive selection. We also found, however, that deleterious mutations were a major driving force in viral evolution during serial passages. Linear relationships between changes in viral fitness and the number of mutations in each MA line demonstrated that some deleterious mutations resulted in fitness decline. Several mutations in MA line 1 were not shared with any of the other four MA lines (PH-1/FgV1, PH-1/FgV1 + 2, PH-1/FgV1 + 3, and PH-1/FgV1 + 4). This suggests that evolutionary pathways of the virus could differ with respect to hosts and also with respect to co-infecting viruses. The data also suggested that the differences among MA lines might also be explained by mutational robustness and other unidentified factors. Additional research is needed to clarify the effects of virus co-infection on the adaptation or evolution of FgV1 to its environments.